A Case Report of Intravascular Hemolysis and Heme Pigment–Induced Nephropathy Following AngioJet Thrombectomy for Thrombosed DIPS Shunt. (December 2020) - Tian, Si; Sinclair, Nicolette; Shah, Sachin
Rationale: The AngioJet system is a combined mechanical and pharmacological device used for thrombectomy. As a result of the mechanical disruption of clot, intravascular hemolysis is noted to occur. Rarely, intravascular hemolysis can be severe enough to cause heme pigment–induced acute kidney injury (AKI). Presenting concerns of the patient: We describe a case of a 45-year-old man with Child-Pugh class B cirrhosis, Budd-Chiari syndrome, and antiphospholipid antibody syndrome who required thrombectomy following a thrombosed direct intrahepatic portosystemic shunt (DIPS). He developed evidence of worsening anemia, dark urine, direct antiglobulin test–negative intravascular hemolysis, and severe AKI within 24 hours of the procedure. Diagnosis: Based on his severe AKI in association with elevated hemolytic markers, and the temporal association with the AngioJet procedure, the patient was diagnosed with heme pigment–induced AKI secondary to intravascular hemolysis. Interventions: The patient remained anuric and became volume-overloaded after fluid resuscitation. He was started on dialysis 72 hours after the procedure. Five days after thrombectomy, hemolytic markers returned to normal. Outcome: The patient received hemodialysis for approximately 3 weeks, followed by renal recovery and cessation of dialysis treatments. Five weeks after the AngioJet procedure, his renal function returned to normal. Teaching points: We present a case of heme pigment–induced AKI following an AngioJet procedure that required initiation of dialysis. Although this rare complication has been reported in the literature, it typically occurs when the procedure is used for larger clot burden (ie, venous thromboembolism). To our knowledge, this is the first case of severe hemolysis with associated AKI following the use of the AngioJet for a thrombosed DIPS. Due to the patient's comorbid conditions, overlapping clinical features, and lack of appreciation of the hemolysis associated with the AngioJet system, the differential diagnosis of the patient's AKI was quite broad. Nephrologists should be aware of this complication when managing patients with AKI to direct therapy early and avoid unnecessary diagnostic and therapeutic interventions.